The birth of new high growth enterprises: Internationalisation through new digital technologies - Mercedes Teruel Carrizosa; Alexander Coad; Clemens Domnick; Florian Flachenecker; Péter Harasztosi; Mario Lorenzo Janiri; Rozália Pál (European Investment Bank (EIB), 2021)
This paper explores the relationship between new digital technologies, internationalisation activity and its impact on High Growth Enterprises (HGEs), using the EIB Group Survey of Investment and Investment Finance and ORBIS data for 27 EU Member States and the United Kingdom. After controlling for sample selection bias, our results suggest that being a HGE is positively associated with the probability that a firm conducts international activities, particularly FDI. Conversely, the internationalisation process seems to trigger strong subsequent firm-growth for FDI. Furthermore, we show evidence on the positive association between firms that are internationalised and those adopting new digital technologies. The adoption of new digital technologies is indirectly related to the status of being a HGE via internationalisation activity in the current period. Our results highlight the complex influence of exporting and FDI on the capacity to become a HGE and the role of new digital technologies in this process.
Keywords: F14; L21; O31; 330; Digital technologies; export; FDI; HGE; internationalisation